Long term outcome of birth asphyxiated infants - Begum, HA; Rahman, A; Anowar, S; Mortuza, A; Nahar, N (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):61-5 The abstract of this article is available on the PubMed website